Per- and polyfluoroalkyl substances (PFAS) in drinking water, gestational diabetes mellitus, hypertension and preeclampsia: A nation-wide register-based study on PFAS in drinking water - Melle Säve-Söderbergh; Irina Gyllenhammar; Tessa Schillemans; Emelie Lindfeldt; Carolina Vogs; Carolina Donat-Vargas; Emilie Helte; Emma Ankarberg; Anders Glynn; Lutz Ahrens; Agneta Åkesson (Environment International)
Background: There is inconclusive evidence of associations between exposure to per- and polyfluoroalkyl substances (PFAS) and diabetes and hypertensive disorders during pregnancy. Objectives: We conducted a nation-wide register-based cohort study to assess the associations of the estimated maternal drinking water exposure to the sum of four major PFAS (PFAS4; perfluorooctane sulfonate (PFOS), perfluorooctanoate (PFOA), perfluorononanoate (PFNA) and perfluorohexanoate (PFHxS)) with gestational diabetes mellitus (GDM), hypertension and preeclampsia. Materials and methods: We included nulliparous women giving birth in Sweden during 2012–2018 in large localities served by municipal drinking water where PFAS were measured in raw and drinking water. Using a one-compartment toxicokinetic model, we estimated cumulative maternal blood levels of PFAS4 during pregnancy considering residential history, municipal PFAS water concentration and year-specific maternal PFAS background serum levels. The outcomes and individual covariates were ascertained via register linkage. Mean values and 95% Confidence Intervals (CI) of Odds Ratios (OR) were estimated by logistic regression. Results: Among the 109,031 nulliparous women included, with an estimated average 7.8 ng PFAS4/mL serum (standard deviation: 2.0 ng/mL), there were indications of a non-monotonic inverse association for PFAS4 and GDM, corresponding to multivariable-adjusted OR 0.72 (95 % CI: 0.61–0.84) when comparing extreme quartiles. An inverse association were also seen for each PFAS individually. No clear associations were seen for hypertension or preeclampsia, although individual PFAS indicated significant associations, both inverse (PFAS and PFHxS) and direct (PFOS and PFNA) for hypertension. Conclusion: In the present study, we observed indications of inverse, non-monotonic associations for PFAS4 and GDM. Some individual PFAS were also associated with hypertension, both direct and inverse. The limitations linked to the exposure assessment still require caution in the interpretation.